Back Cover: Single‐Molecule 3D Orientation Imaging Reveals Nanoscale Compositional Heterogeneity in Lipid Membranes (Angew. Chem. Int. Ed. 40/2020). Issue 40 (31st August 2020) - Lu, Jin; Mazidi, Hesam; Ding, Tianben; Zhang, Oumeng; Lew, Matthew D.
Abstract : The rotational dynamics of single fluorescent dyes are influenced by their surrounding nano‐environment within lipid membranes. In their Research Article on page 17572, M. D. Lew and co‐workers show that super‐resolved imaging of molecular orientation and wobble in 3D resolves lipid composition, liquid‐ordered and ‐disordered phases, and enzyme activity in membranes.